PENERAPAN METODE PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN KONSENTRASI SISWA PADA MATA PELAJARAN PKN KELAS XI DI SMAN 1 BLEGA - Holipah; Ernawati; Bagus Imam Faisal; Diah Retna Yuniarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine whether the implementation of the role playing method can increase students' concentration in civics learning at SMAN 1 Blega. The study employs a descriptive qualitative approach with 32 students from class XI as research subjects. Data collection techniques include observation through teaching module implementation sheets and student learning concentration questionnaires. The results indicate that the implementation of the PKn teaching module using the role-playing method is in the "good" category with an 80% percentage. The highest indicator is the teacher's ability to respond to student questions, reaching 100%, while the lowest indicators relate to initial motivation, aperception, and linking material to social life, each achieving 70%. Meanwhile, students' learning concentration reaches 88%, which is in the "very good" category. The five highest concentration aspects achieve 91%, including attention to teacher explanations, resilience against distractions, focus during discussions, attention during role-playing, and seriousness in participation. The relatively lower aspects are the ability to focus attention when the teacher asks questions (83%) and the ability to avoid other thoughts during learning (80%), both of which remain in the "good" category. This research concludes that the role-playing method is effective in improving the quality of lesson implementation while enhancing student concentration, particularly on PKn material about the formulation of Pancasila in the BPUPKI session. Students demonstrated the ability to maintain focus throughout the learning process, follow activities well, and actively participate in role-playing. Thus, the application of the role-playing method in PKn learning provides tangible support for students to be more focused, active, and enthusiastic in engaging in the teaching and learning process, making learning more meaningful, contextual, and enjoyable.